An assessment of the potential for transformational market growth amongst the critical metals. (2nd January 2016) - Sykes, J. P.; Wright, J. P.; Trench, A.; Miller, P.
Abstract : A 'critical metal' is one that has important economic uses, but which also faces supply risks for geopolitical or environmental and sustainability reasons. The constrained nature of critical metals supply means proposed solutions to the problem commonly involve reducing demand and therefore reliance, via recycling, substitution and thrifting. However, most critical metals are presently only small markets and therefore such an approach ignores the potential of transformational market growth to reduce supply risk, by creating large, diverse, transparent markets with multiple sources of primary mine supply, akin to modern base metals markets. Research is therefore required into which critical metals have the greatest potential for such transformational market growth. This study therefore conducts an evaluation of 49 critical metals to determine which are nearest to the combined breakthroughs in discovery, supply and demand that may lead to transformational market growth. The study concludes that 13 markets from the 49 critical metals, being magnesium, silicon, barium, boron, lithium, cobalt, chromium, vanadium, gallium, strontium, cerium, lanthanum and scandium have the highest potential for transformational market growth and thus efforts to resolve supply risk in these markets may be better focussed on overcoming current market constraints and growing these markets, rather than lessening reliance by reducing demand.